(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
STEM (Science, Technology, Engineering, and Mathematics) fields rely heavily on academic writing for the communication of research, innovation, and collaboration. However, many students and professionals, particularly non-native English speakers, face significant linguistic challenges when writing in academic English. This article explores the core linguistic difficulties encountered in STEM academic writing, such as mastering discipline-specific vocabulary, handling syntactic complexity, achieving appropriate tone and style, and meeting discourse and rhetorical expectations. Solutions and pedagogical implications are also discussed, providing insight into how educators and learners can overcome these barriers for clearer and more effective scientific communication.